2017
DOI: 10.2147/copd.s130416
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leukocyte microRNAs as novel biomarkers for COPD

Abstract: COPD is a multifactorial disease caused by environmental determinants as well as genetic risk factors. The prevalence and mortality of COPD continue to increase, and underdiagnosis of COPD remains a critical issue. Previous reports investigated promising microRNAs (miRNAs) to reveal the molecular mechanism for the development of COPD; however, diagnostic and therapeutic markers for COPD have not yet been found. For this study, 20 representative COPD patients were separated into four groups based on increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
0
17
1
Order By: Relevance
“…Finally, the combined expression of hsa-miR-195 and hsa-miR-143, obtained from databases, is able to identify lung cancer compared to disease-free status, but cannot distinguish COPD from lung cancer ( 176 ). From peripheral leucocytes, differential expression of miR-106b-5p, miR-183-5p, miR-125a-5p, and miR-100-5p was found in COPD compared to healthy controls, and miR-106b-5p was directly correlated with disease severity alleviation ( 88 ). Several studies have focused their interest on miRNAs from specific immune system cells exploring the implication of these structures in processes linked to asthma or COPD.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…Finally, the combined expression of hsa-miR-195 and hsa-miR-143, obtained from databases, is able to identify lung cancer compared to disease-free status, but cannot distinguish COPD from lung cancer ( 176 ). From peripheral leucocytes, differential expression of miR-106b-5p, miR-183-5p, miR-125a-5p, and miR-100-5p was found in COPD compared to healthy controls, and miR-106b-5p was directly correlated with disease severity alleviation ( 88 ). Several studies have focused their interest on miRNAs from specific immune system cells exploring the implication of these structures in processes linked to asthma or COPD.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…From the results of the miRNA PCR array and replication cohort, we successfully identified miR‐15b‐5p as a novel biomarker for ACO. Several studies have described the difference in miRNA levels between patients with asthma or COPD and healthy controls 12‐15 . However, few studies have examined the difference in miRNA expression levels between ACO, asthma, and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are easily detectable due to their stability in serum as they are resistant to degradation and are highly detectable by quantitative PCR, microarrays and miRNA sequencing. W ang et al [ 101 ] found that miR-106b-5p could be a biomarker of COPD severity. However, more about miR-106b-5p must be understood to elucidate any mechanism, as it has come up in several miRNA serum studies, including carcinogenesis.…”
Section: Biological Markers and The Evolution To Endotypic Therapymentioning
confidence: 99%